Is there any association between microalbuminuria and Parkinson’s disease? - Alpua, Murat; Kisa, Ucler (Annals of Medical Research, 2021)
Aim: To investigate microalbuminuria in patients with Parkinson’s disease (PD) and to determine its relationship with the stages of the disease. Parkinson’s disease (PD) is a chronic neurodegeneration of dopaminergic neurons in the substantia nigra. The reason for the death of these neurons is still unclear; however, studies have demonstrated the potential involvement of mitochondria, endoplasmic reticulum in contributing to cellular oxidative stress.Material and Methods: Thirty-two PD patients who admitted to Neurology Clinic of Kirikkale University’s Medical Faculty and 30 healthy volunteers whose age and sex-matched were included in the study. Urine creatinine and urine albumin levels were determined in patient and healthy groups. The disease duration and Hoehn and Yahr stages were recorded.Results: There was no statistically significant difference between urine creatinine, microalbumin, and urine creatinine/albumin ratios when PD patient results compared with the healthy volunteers’. There was no significant correlation among urine creatinine, microalbumin, and urine creatinine/albumin ratio between the disease duration and Hoehn and Yahr staging in patients with PD.Conclusion: Microalbuminuria is an indirect finding of oxidative stress in urine. In the current study, microalbuminuria was not detected in PD patients at various stages of the disease. It is an important finding that microalbuminuria, a marker of oxidative stress in the urine in PD, a disease in which oxidative stress plays a significant role in etiopathogenesis, is not found.Keywords: Hoehn and Yahr Scale;microalbumin; oxidative stress; Parkinson’s disease; Urine creatinine.
Keywords: Hoehn and Yahr Scale; microalbumin; oxidative stress; Parkinson’s disease; Urine creatinine.